Life Insurance Sector in India ; A Bird Eye View (International Journal of Food and Nutritional Sciences, 2022)
Life Insurance plays a pivotal role in human's life. Though the insurance industry is in existence since long, level of awareness towards the life insurance is negligible. The study tries to understand the awareness of the people towards life insurance products after the privatization of the insurance sector.